Treatment Strategy for Chronic Obstructive Parotitis Related to Diabetes: A Retrospective Analysis of 12 Cases - Wu, Chuan-Bin; Xue, Lei; Zhou, Qing (Frontiers in Pharmacology, 2022)
Objectives: The aim of this study was to describe our experience in treating chronic obstructive parotitis (COP) related to diabetes. Methods: Twelve patients with COP related to diabetes were selected for the study. A sialendoscope was introduced from the orifice to investigate the ductal wall and lumen. During the operation, chymotrypsin and gentamicin were injected. All patients were followed up for 6 months. Preoperative and postoperative visual analog scale (VAS) evaluations and salivary gland scintigraphy (SGS) examinations were applied to evaluate the therapeutic effect; differences were considered statistically significant at P < 0.05. Results: A sialendoscope was successfully used under local anesthesia in all members of the cohort. As shown by the endoscope, mucus plugs were the most common feature. Some adhered tightly to the ductal wall. We also found ductal congestion in some cases. The postoperative VAS scores and SGS counts were both significantly lower than the preoperative values (P < 0.05). Conclusion: Chymotrypsin administration during interventional sialendoscopy is significantly effective in the treatment of diabetes-related COP.